2020
DOI: 10.1111/anu.13177
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of purine nucleotides adenosine, guanosine and inosine monophosphates as functional supplements on growth and health performances of red sea bream,Pagrus majorjuvenile

Abstract: Purine nucleotides regulate the cellular functions in the animal body. The current study evaluates the comparative efficacy of dietary purine nucleotides, that is, adenosine monophosphate (AMP), guanosine monophosphate (GMP) and inosine monophosphate (IMP) in red sea bream Pagrus major. Semi‐purified basal diet was formulated (Control, D1) containing 550 g/kg protein, supplemented with purine nucleotides AMP, GMP and IMP at their optimum supplementation level (2, 4 and 4 g/kg) to formulate the experimental die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In contrast, supplementation of 1.5 to 4.0 g/kg purified nucleotides in casein-based diet significantly promoted growth of juvenile grouper Epinephelus malabaricus and red sea bream (Hossain et al, ,2016(Hossain et al, , , 2016a(Hossain et al, , , 2016b(Hossain et al, , , 2017a(Hossain et al, , , 2017bLin et al, 2009). The inconsistence findings on the growth promotion effect of dietary nucleotides could be associated with the different protein source and supplementation level of nucleotides Hossain et al, (2021) reported that variation of nucleotide types also affected response variations in terms of growth, feed utilization, immune responses and stress tolerance of fish. In addition, growth and feed utilization of fish were also not affected by replacing 75% fish oil by vegetable oils in the present study.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast, supplementation of 1.5 to 4.0 g/kg purified nucleotides in casein-based diet significantly promoted growth of juvenile grouper Epinephelus malabaricus and red sea bream (Hossain et al, ,2016(Hossain et al, , , 2016a(Hossain et al, , , 2016b(Hossain et al, , , 2017a(Hossain et al, , , 2017bLin et al, 2009). The inconsistence findings on the growth promotion effect of dietary nucleotides could be associated with the different protein source and supplementation level of nucleotides Hossain et al, (2021) reported that variation of nucleotide types also affected response variations in terms of growth, feed utilization, immune responses and stress tolerance of fish. In addition, growth and feed utilization of fish were also not affected by replacing 75% fish oil by vegetable oils in the present study.…”
Section: Discussionmentioning
confidence: 95%
“…The inconsistence findings on the growth promotion effect of dietary nucleotides could be associated with the different protein source and supplementation level of nucleotides in the experimental diet. Moreover, recently, Hossain et al, (2020), Hossain et al, (2021) reported that variation of nucleotide types also affected response variations in terms of growth, feed utilization, immune responses and stress tolerance of fish. In addition, growth and feed utilization of fish were also not affected by replacing 75% fish oil by vegetable oils in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, certain FuFAs are inexpensive and provide improved performance. Hossain et al 361 reported that among individual purine NTs (IMP, GMP, and adenosine monophosphate [AMP]), IMP is less expensive (25 g = $197.5) than AMP (25 g = $377.6) or GMP (25 g = $463.0) and therefore, IMP is a more economically feasible and effective purine NT for red sea bream. Apart from depending on commercial FuFA products, to reduce cost, some FuFA materials can be prepared from locally available inputs.…”
Section: Economic Evaluation Of Fufa: Is It Economic or Just Ecologic...mentioning
confidence: 99%